The degree to which male and female teachers in Mafraq city schools possess the requirements and obstacles of electronic training from the point of view of a random sample of them - Al-Sharafat, Tayel Munawwar Kasab (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to know the level of electronic training and its impact on male and female teachers in the three districts of Mafraq and the obstacles they face. The researcher used the descriptive survey method, where he developed a questionnaire of (16) items, equally divided into two areas; Training (8) phrases and obstacles to training (8) phrases. It was applied to a random sample of (112), including (66) male and (46) female teachers, and the results revealed that the degree of possession of male and female teachers in Mafraq city schools for the requirements of electronic training obtained a total average of (3.71), i.e. with a degree of possession (great). Obstacles to electronic training, and it obtained an average of (3.40), meaning a degree of (medium) disability, and based on the results, the researcher made a number of recommendations to develop the electronic skills of male and female teachers in Mafraq and the whole of the Kingdom of Jordan, in addition to suggestions for complementary studies on the subject.